Teacher Evaluation in Determining Ability Minimum Completeness Criteria Subject First High School Mathematics - Subekti, Estu; Rusilowati, Ani; Khumaedi, M. (Universitas Negeri Semarang, 2019)
KKM determines a measurement of the quality of learning in the educational unit. Carrying capacity, intake, students, and teachers use the complexity of determining the subjects of mathematics so KKM in education units can be different. This study aimed to evaluate the ability of teachers to include suitability procedures, enabling and inhibiting factors as well as the enforceability of the process in determining the KKM. The study used a survey method. CIPP evaluation model using the model. The sampling technique using techniques Slovin. The subjects are mathematics teachers of junior high school in Cirebon. Content validity of the instrument based on the judgment of experts using a formula Aiken's V and reliability testing using the formula Ebel. Content validity was tested by three experts. Data is collected using interview techniques, documentation, and questionnaires. Data were analyzed quantitatively and qualitatively. The ability of teachers by 83% with a very high category. Suitability procedures by 85% with a very high category and is not by following under accordance with the procedures as much as 15% lower categories. Supporting factor of 92% with a very high category and a limiting factor of 8% with the lower categories. The supporting factors include improvements to the learning process with the fulfillment of infrastructure, making document 1, 2 and 3, the achievement of KKM conducted jointly, their results are difficult KD analysis, moderate or easy, proactive learners, participating in learning activities and tasks that have been designed educators, KD producing appropriate evaluation questions. Inhibiting factors there is no standard minimum completeness criteria format that is produced through MGMP. Implementation process by 79% with a very high category.